Pengaruh Social Media Influencer, Brand Awareness, dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Ms Glow di Denpasar - Yanti Yuliastiawati, Ni Kadek; Lasmi, Ni Wayan (Economic Reviews Journal, 2025)
This study aims to analyze and test the effect of Social Media Influencers, Brand Awareness, and Product Quality on the Purchase Decision for MS GLOW skincare products in Denpasar City. Employing a quantitative approach, the study involved 96 MS GLOW consumer respondents in Denpasar, with data analyzed using multiple linear regression via the SPSS program. The results indicate that partially, the variables Social Media Influencer (Sig. 0.001), Brand Awareness (Sig. 0.005), and Product Quality (Sig. 0.000) all have a positive and significant effect on Purchase Decisions. Simultaneously, all three variables also have a significant effect on Purchase Decisions. It was found that Product Quality is the most dominant variable affecting the Purchase Decision with the highest regression coefficient (B=0.476), and the ability of the three independent variables to explain the Purchase Decision is 51.8% (Adjusted R Square = 0.518).